PERKEMBANGAN JALAN RAYA DI PANTAI UTARA JAWA TENGAH SEJAK MATARAM ISLAM HINGGA PEMERINTAHAN DAENDELS - Hartatik, Endah Sri (Paramita: Historical Studies Journal, 2016)
This article analyze the development of the highway on the north coast of Central Java since the Islamic Mataram in the 17th century to the reign Daendels in the 19th century. This period is very important to know the emergence and development of highways who played a major role in the development of society in Java. Highway is a significant transportation in Java. The most important highway in Java is in the northern coast of Central Java. The highway has long historical roots, formerly the coastal highway then developed to be the post highway. The transformation process from the coastal highway to the post highway passed through a political process since Daendels governed Java in 1808. For the armed forces and economy exploitation, then it was established The Post Highway. In Central Java, the highway was built based on the coastal highway. Revitalization and transformation of the highway had caused economy development in the areas of cities and villages integrated by the highway networks and facilitated the administrative control for colonial rulers. Tulisan ini bertujuan menganalisis perkembangan jalan raya di pantai utara Jawa Tengah sejak masa Mataram Islam di abad ke-17 sampai pemerintahan Daendels di abad ke-19. Periode ini sangat penting sebagai landasan historis perkembangan jalan raya pada periode setelahnya. Jalan raya merupakan  sarana transportasi penting di  Pulau Jawa. Salah satu jalan raya terpenting di Jawa adalah Jalan Raya di Pantai Utara Jawa Tengah. Jalan Raya ini memiliki akar historis yang panjang, semula merupakan Jalan Raya Pesisir kemudian berkembang menjadi Jalan Raya Pos. Proses transformasi dari Jalan Raya Pesisir menjadi Jalan Raya Pos melalui proses politik ketika Daendels menguasai Jawa pada tahun 1808. Untuk kepentingan angkatan perang dan eksploitasi ekonomi dibangunlah Jalan Raya Pos. Di Jawa Tengah  jalan raya tersebut  dibangun dengan  mendasarkan diri pada Jalan Raya Pesisir. Revitalisasi dan transformasi jalan raya itu telah mengakibatkan perkembangan ekonomi di wilayah kota-kota dan desa-desa yang terintegrasi oleh jaringan jalan raya tersebut serta mempermudah kontrol administrasi bagi penguasa kolonial.